As razões contra-indutivistas de Karl Popper - Valdirlen do Nascimento Loyolla (2003)
Karl Popper's (1902-1994) main opiutcniological preoccupation, in the first phase of his thought (The logic of scientific discovery and Realism and the aim of the science) , dcalo with the elucidation of the value of scientific theoriea. In thin manner, he contributed decisively for the solution of tlie indviction problem and its importance to Science. Justificationists (inductionists and neopositivists) think that the r;\tion;il justification of induction is extremely important becauoo if wo cannot justify induction we have to accept that scientific knowlccJqe in baseless. David Hume (1711-1776) has demonstrated we cannot juntify induction rationally. On the other hand, neopositivists believe tlu; inductive inferences may be rationally justified. In thin context, we ihall present the general plan of the Popperian critical reanonn, not just in order to eliminate induction but in order to reject any strategy of justificationism in Science.